Investigation of head covering and thermal comfort in radiant cooling Malaysian offices - Neama, Saaeed (Faculty of Design & Architecture, Universiti Putra Malaysia, 2013)
This study investigated the head covering in a radiant cooling Malaysian office building. We studied the Energy Commission’s Diamond Building in Putrajaya, which is equipped with radiant slab cooling. The objective was to determine the effectiveness of head covering on thermal comfort. We adopted the assessment procedure from the ASHRAE 55 and the ISO 7730 standards and applied to the building’s second and sixth floors and analysed the data through cross tabulation. We collected 132 data sets completed by 49 participants continuously for four days (two days for each floor) during working hours. The survey was the results of two online questionnaires (a background survey and a daily survey). In the dissatisfaction with overall thermal environment and actual mean vote, the analysis showed a strong correlation between head covering and discomfort (warmer feel) (V = .5, p<.01). We correlated the head covering with all of the independent variables in the background and daily surveys. Females outnumbered male in wearing a head covering (V = .8, p<.001). Wearing a head covering was not affected by age(V = .3, p > .05). Wearing a head covering does not affect subjects’ dissatisfaction with floor temperature (V = .3, p> .5). Person who wore a head covering preferred increased air speed (V = .4, p< .05). Wearing a head covering increased the sweating (V = .3, p< .05).In conclusion, wearing a head covering affects thermal comfort in radiant cooling office building